2018
DOI: 10.1007/s10694-018-0706-2
|View full text |Cite
|
Sign up to set email alerts
|

Flame Heights and Heat Transfer in Façade System Ventilation Cavities

Abstract: Abstract. The design of buildings using multilayer constructions poses a challenge for fire safety and needs to be understood. Narrow air gaps and cavities are common in many constructions, e.g. ventilated fac¸ade systems. In these construction systems flames can enter the cavities and fire can spread on the interior surfaces of the cavities. An experimental program was performed to investigate the influence of the cavity width on the flame heights, the fire driven upward flow and the incident heat fluxes to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…[3][4][5][6] In recent years, several research studies have investigated the fire performance of ventilated façade systems and shown that flame spread through the air cavity of a ventilated façade can be several times higher than that along the outside the facade. 4,5 Furthermore, the presence of an air cavity tends to increase the energy released by the facade system. 6 Thus, both the materials taken independently and the whole system (combination of materials and assembly) are potentially a source of propagation of a fire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] In recent years, several research studies have investigated the fire performance of ventilated façade systems and shown that flame spread through the air cavity of a ventilated façade can be several times higher than that along the outside the facade. 4,5 Furthermore, the presence of an air cavity tends to increase the energy released by the facade system. 6 Thus, both the materials taken independently and the whole system (combination of materials and assembly) are potentially a source of propagation of a fire.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of fire safety, it should be noticed that for systems such as ETICS or ventilated façades, the materials used (cladding or insulation) may be combustible . Moreover, in ventilated facades, the air gap may be a vector of fire propagation through chimney effect . In recent years, several research studies have investigated the fire performance of ventilated façade systems and shown that flame spread through the air cavity of a ventilated façade can be several times higher than that along the outside the facade .…”
Section: Introductionmentioning
confidence: 99%
“…In the context of fire safety, it should be noted that for systems such as external thermal insulation composite systems (ETICS) or ventilated facades, the materials used (cladding or insulation) may be combustible. In addition, in ventilated facades, the air gap may be a vector of fire propagation via the chimney effect , . Thus, both the materials taken independently and the system as a whole (combination of materials and assembly) can potentially contribute to fire propagation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in ventilated facades, the air gap may be a vector of fire propagation via the chimney effect. 5,[7][8][9]10 Thus, both the materials taken independently and the system as a whole (combination of materials and assembly) can potentially contribute to fire propagation.…”
mentioning
confidence: 99%
“…These varying configurations have led to a series of issues regarding their hydrothermal, energy, sound and fire performance. 10 Construction details (eg, cladding fixings) 8 or fire barriers 11,12 may also affect flame spreading within the ventilation air cavity.…”
Section: Ventilated Façade Systemmentioning
confidence: 99%